Pathogenic and academic succession of therapeutic efficiency of functional conditions in women - P. V. Budanov; S. A. Levakov; N. A. Sheshukova; T. V. Shemanaeva (Лечащий Врач, 2021)
Menstrual disorders, preliminary pregnancy planning require safe prevention and careful support of reproductive function. Bioregulatory therapy based on the principle of activation of intrinsic reserves of the organism meets these requirements.